Efeito da revascularização renal sobre a evolução da disfunção renal na nefropatia isquêmica aterosclerótica - Hagemann, Rodrigo [UNESP] (2014)
Chronic kidney disease (CKD) is characterized by a progressive loss of renal function and its main causes are hypertension and diabetes mellitus. Among the causes of hypertension is atherosclerotic renal disease (ARD). The development of CKD in patients with ARD appears to be due not only to the involvement of the main renal arteries, but also of the renal microcirculation, which may explain the fact that the success of the procedure does not guarantee an improvement in the progression of CKD. To date there is no evidence of benefit of angioplasty compared to medical treatment alone in patients with ARD. The present paper analyzes the most significant studies on renal outcomes in patients with ARD undergoing revascularization or medical treatment alone.